Reducing musculoskeletal disorders by “t” and “chi-square” statistical analyses - Akter, Sharmin; Urmee, Sharmin Akter; Parvez, Md Shohel; Islam, Riadul (Review of Industrial Engineering Letters, 2025)
Students spend a significant amount of time in the classroom and university library, mostly sitting. Prolonged sitting in incorrect posture and on inappropriate furniture can cause serious musculoskeletal disorders (MSDs) such as back injuries, neck and shoulder pain, ligament injuries, etc. This study aimed to design ergonomic furniture for both classrooms and libraries. To fulfill this objective, a total of 300 students (aged 19-24 years) were randomly selected from 10 different departments. Fifteen anthropometric measurements (popliteal height, stature, sitting eye height, sitting height, sitting elbow height, thigh clearance, knee height, buttock-knee height, elbow-to-elbow breadth, hip breadth, sitting shoulder height, sitting lowest rib bone height, sitting upper hip bone height, forearm fingertip length, buttock-popliteal length) and eleven furniture dimensions were selected and evaluated to identify potential mismatches between them. Moreover, "t" and "chi-square" statistical analyses were performed to compare the users’ body measurements and furniture dimensions. Results showed that a significant level of mismatch was found between the body measurements and furniture dimensions. The results also indicated that the students’ anthropometric measurements and the existing furniture dimensions were distinct. Finally, this study proposed redesigned academic furniture according to users’ anthropometric measurements, which will reduce MSD problems among students.